1993
DOI: 10.1002/anie.199301011
|View full text |Cite
|
Sign up to set email alerts
|

A Short, Linear Synthesis of (9S)‐Dihydroerythronolide A

Abstract: Recently Mulzer['' characterized the efforts directed toward the synthesis of erythronolides as a "never-ending story". which is even more amazing as there is no direct need for such syntheses. The motivation is found elsewhere: Since 1956 when Woodward gave his famous appraisal of erythromycin,12] erythronolide syntheses have become the yardstick for measuring progress in the efficiency of stereoselective synthesis. Almost all of the published syntheses or attempted syntheses of erythronolides A and B were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Modifications include acylation of hydroxy groups, deacylation, aldehyde or ketone reduction, double bond reduction, and N-demethylation . More fundamental structural changes require synthesis of macrolide analogues from simple building blocks, and over the past few years four general approaches have been developed to control the critical stereochemistry: (i) ring-cleavage, where the appropriate stereorelationship of the asymmetric centers is first secured by using the conformational bias of a small or medium sized ring, which is then opened to give an acyclic fragment with the stereocenters correctly related, (ii) exploitation of the existing asymmetric centers and functionalities of a carbohydrate precursor, (iii) stereoselective introduction of new asymmetric centers on an acyclic precursor, and (iv) stereoselective introduction of new asymmetric centers onto an intact macrocyclic precursor, using the conformational bias of the macrocycle . Additional problems in the total synthesis of macrolide analogues are the macrolactonization step and the stereo- and regiocontrolled attachment of the appropriate basic or neutral deoxysugars.…”
Section: Introductionmentioning
confidence: 99%
“…Modifications include acylation of hydroxy groups, deacylation, aldehyde or ketone reduction, double bond reduction, and N-demethylation . More fundamental structural changes require synthesis of macrolide analogues from simple building blocks, and over the past few years four general approaches have been developed to control the critical stereochemistry: (i) ring-cleavage, where the appropriate stereorelationship of the asymmetric centers is first secured by using the conformational bias of a small or medium sized ring, which is then opened to give an acyclic fragment with the stereocenters correctly related, (ii) exploitation of the existing asymmetric centers and functionalities of a carbohydrate precursor, (iii) stereoselective introduction of new asymmetric centers on an acyclic precursor, and (iv) stereoselective introduction of new asymmetric centers onto an intact macrocyclic precursor, using the conformational bias of the macrocycle . Additional problems in the total synthesis of macrolide analogues are the macrolactonization step and the stereo- and regiocontrolled attachment of the appropriate basic or neutral deoxysugars.…”
Section: Introductionmentioning
confidence: 99%
“…Woodward et al,1b Yonemitsu et al,7 Hoffmann et al,18 and Woerpel et al19 have independently reported the effective macrolactonization of seco‐acids 11a and 11b (R 1 Mes, R 2 H) in Figure 2, as well as 11d and 11e (R 1 PMP, R 2 H) in Scheme which have structures similar to that of the present seco‐acid 11c (R 1 Ph, R 2 H) in Figure 2, therefore, it is assumed that the MNBA lactonization could also be applicable to the cyclization of these kinds of seco‐acids to give the corresponding lactones in high yields.…”
Section: Resultsmentioning
confidence: 99%
“…Advancement into the Trans Series. With technology available for the preparation of 30 in quantity, this advanced intermediate was oxidized with DDQ in dry ether containing 4 Å molecular sieves . As a consequence of the presence of a neighboring free hydroxyl, the benzylic carbocation so generated was trapped intramolecularly to provide the PMP acetal 31 (Scheme ).…”
Section: Resultsmentioning
confidence: 99%